Ammonia capture from the gas phase by encapsulated ionic liquids (ENILs). Issue 66 (28th June 2016) - Lemus, Jesus; Bedia, Jorge; Moya, Cristian; Alonso-Morales, Noelia; Gilarranz, Miguel A.; Palomar, Jose; Rodriguez, Juan J.
Abstract : Encapsulated ionic liquids (ENILs) based on carbonaceous submicrocapsules were designed, synthesized and applied to the sorption of NH3 from gas streams. Abstract : Encapsulated ionic liquids (ENILs) based on carbonaceous submicrocapsules were designed, synthesized and applied to the sorption of NH3 from gas streams. The ENILs were prepared using three different task-specific ILs with adequate properties for NH3 capture: 1-(2-hydroxyethyl)-3-methylimidazolium tetrafluoroborate (EtOHmimBF4 ), choline bis(trifluoromethylsulfonyl)imide (CholineNTf2 ) and tris(2-hydroxyethyl)methylammonium methylsulfate [(EtOH)3 MeNMeSO4 ]. The ENILs synthesized were analyzed by different techniques to assess their morphology, chemical composition, porous structure and thermal stability. The capture of NH3 was tested in fixed-bed experiments under atmospheric pressure. The influence of the type and load of IL, temperature (30, 45 and 60 °C) and NH3 inlet concentration was analyzed. Desorption of NH3 from the exhausted ENILs was also studied at atmospheric pressure and temperatures in the range of 150 to 200 °C. The ENILs prepared with task-specific ILs were found to be suitable for NH3 capture in the fixed-bed operation. These systems can be a promising alternative to conventional absorption or adsorption due to: (i) high sorption capacity controlled by IL selection, (ii) remarkable mass transfer rate, (iii) low sensitiveness to high temperatures of the gas stream, (iv) fast and complete regeneration of the exhausted ENIL at mild conditions; and (v) recovery of NH3 .